2009
DOI: 10.1245/s10434-009-0386-8
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Versus Open Subtotal Gastrectomy for Adenocarcinoma: A Case–Control Study

Abstract: Laparoscopic subtotal gastrectomy for adenocarcinoma is comparable to the open approach with regard to oncologic principles of resection, with equivalent margin status and adequate lymph node retrieval, demonstrating technically feasibility and equivalent short-term recurrence-free survival. Additional benefits of decreased postoperative complications, decreased length of hospital stay, and decreased narcotic use make this a preferable approach for selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
120
1
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(146 citation statements)
references
References 27 publications
13
120
1
12
Order By: Relevance
“…Patients with a BMI of more than 30 were excluded from this study; as a result, the median BMI was 21.8. In western countries, the median BMI was reported as 26-29, and higher morbidities (10%-26% as grade 1-4 adverse events) than that in this study (9.1%) were demonstrated [22,23]. Thus, BMI should be taken into consideration to interpret the morbidity results.…”
Section: Discussionmentioning
confidence: 51%
“…Patients with a BMI of more than 30 were excluded from this study; as a result, the median BMI was 21.8. In western countries, the median BMI was reported as 26-29, and higher morbidities (10%-26% as grade 1-4 adverse events) than that in this study (9.1%) were demonstrated [22,23]. Thus, BMI should be taken into consideration to interpret the morbidity results.…”
Section: Discussionmentioning
confidence: 51%
“…After reading the full texts of the remaining papers, 24 studies were removed as they only reported the outcomes of LG for AGC whereas no controlled or matched cases treated by OG were available. Among the remaining articles, 19 studies [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] were excluded because EGC cases were mixed with AGCs in the cohort studies and data on AGCs were not extractable. Eight studies were further deleted for the following reasons: 2 studies were ongoing randomized controlled trials (RCTs) that only described study design and patient enrollment criteria without results reported [56,57]; 2 studies had overlapped enrollments with former research [58,59]; 1 study reported incomplete data that were not suitable for analysis [60]; and 3 studies discussed other issues irrelevant to the topic of this meta-analysis [61][62][63].…”
Section: Resultsmentioning
confidence: 99%
“…If the feasibility and safety of LGS in the treatment of EGC has been proven, it is also true that several reports have shown the efficacy of LGS in the cure of EGC with results comparable to those of an OGS series [11,12] .…”
Section: Lgs (N = 22) Ogs (N = 25) P Valuementioning
confidence: 99%